Solar Power Integration Into the Transmission Network for Reducing Power Loss and Optimizing Generation Costs – A Comparative Analysis: Online First: 13/05/2026 - Vo Thanh Thang; Nguyen Trung Thang; Nguyen Thuy Hang; Le Chi Kien (Journal of Technical Education Science, 2026)
This paper investigates the integration of Solar Power Plants (SPP) into transmission grids through comparative assessment of two single-objective approaches: minimization of power loss and minimization of generation costs, while maintaining system operational safety conditions. Using the Particle Swarm Optimization algorithm on a modified IEEE 30-bus test system, the study sequentially determined the optimal SPP capacity and location for each objectives separately. The findings reveal that strategic placement and sizing are paramount, confirming that system benefits are non-linear with capacity increases and that the optimal bus location is highly site-specific. Crucially, comparative analysis demonstrates the clear superiority of the generation cost minimization objective. This economic-centric strategy not only achieves the largest reduction in total system cost but also concurrently provides superior technical performance by significantly reducing power losses. This dual success is achieved because the optimization algorithm exploits the locational value and zero-fuel-cost characteristic of solar power, inherently guiding the system toward an operating point that is both economically optimal and physically efficient. This research establishes a core principle for modern smart-grids: the most economically efficient design consistently delivers the most technically robust solution.